A new calculation technique for onboard progressive flooding simulation. Issue 3 (2nd September 2019) - Braidotti, Luca; Mauro, Francesco
ABSTRACT: During a flooding emergency, the master has to take hard decisions with serious impact on passengers and crew safety. A fast and reliable time domain simulation of the progressive flooding process can significantly aid the master in choosing the right counteractions immediately after the damage occurrence. In last decades many methods to simulate progressive flooding have been developed with increasing precision, but most of them require too much computational effort being not suitable for a direct onboard application. This paper presents a novel quasi-static simulation technique capable to provide accurate results in a reasonable calculation time. The analytical solution of the linearised system of governing differential equations allows to extend the time step over the intrinsic limits of numerical integration methods without affecting accuracy. The approach has been compared with numerical integration of non-linear system of equations and a recent pressure correction technique on a box-barge test case available in the literature.